Preventive Maintenance Analysis on Stationery Spot Welding - Solihin Solihin; Murwan Widyantoro; Al Munawir (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2021)
AbstractMaintenance is all activities needed to maintain or maintain the quality of equipment or machines to keep them functioning properly, for that maintenance is very important at PT. XYZ.Smooth production is highly dependent on the reliability and readiness of the machine, therefore a maintenance policy is needed by determining the priority of the machine to be maintained so that the reliability of the machine is maintained. The machine under study is the Stationery Spot Welding machine for both assy parts and body parts. The distribution model used is the exponential distribution model, from the form of the data it can be determined treatment. The data needed are machine working hours data, corrective maintenance time data, SDT (supply delay time) and ADT (administrative delay time) data, as well as preventive maintenance data. From the exponential distribution pattern, the cumulative function values, lamda, machine reliability, MTBF (mean time between failure), MTBM (mean time between maintenance), machine readiness time (availability) for each machine will be obtained. From the results of data processing, the reliability of the Stationery Spot Welding machine type SSW-35-Ndz, type SSW-50-Ndz, and type SSW-70-Ndz is 36.7%. This shows a very low level of reliability, therefore preventive maintenance is needed. In addition to reliability, MTBM is also obtained as a preventive maintenance schedule on the SSW-35-Ndz engine once every 1023 hours, the SSW-50-Ndz engine every 628 hours and the SSW-70-Ndz engine every 628 hours. Keywords : Maintenance, Preventive, Reliability, MTBF, MTBM